2005
DOI: 10.1182/blood.v106.11.3655.3655
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo Controlled, Double Blind Trial of the Effect of Combined Therapy with Deferoxamine and Deferiprone on Myocardial Iron in Thalassaemia Major Using Cardiovascular Magnetic Resonance.

Abstract: Introduction: Beta thalassaemia major (TM) is a hereditary anaemia affecting 60 000 births worldwide each year. Survival is dependent upon lifelong blood transfusions with cardiac failure secondary to myocardial iron loading being the commonest cause of death. Conventional treatment with the parenteral iron chelator deferoxamine improves mortality but prognosis remains poor and it has been reported that approximately two-thirds of patients maintained on this treatment have myocardial iron loading. More recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…This was surprising given the efficacy of DFP in alleviating cardiac iron‐loading in patients with thalassemia (Pennell et al , ). In view of the lack of improvement in cardiac iron‐loading, and evidence of efficacy of combined chelation therapy in accelerating removal of cardiac iron in patients with thalassemia (Tanner et al , ), deferoxamine was started at a dose of 45 mg/kg, given as a 10‐h subcutaneous infusion twice per week. MRI scans after commencement of the dual regimen demonstrated improved cardiac iron loading (20 ms), with no evidence of progression of ironloading in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was surprising given the efficacy of DFP in alleviating cardiac iron‐loading in patients with thalassemia (Pennell et al , ). In view of the lack of improvement in cardiac iron‐loading, and evidence of efficacy of combined chelation therapy in accelerating removal of cardiac iron in patients with thalassemia (Tanner et al , ), deferoxamine was started at a dose of 45 mg/kg, given as a 10‐h subcutaneous infusion twice per week. MRI scans after commencement of the dual regimen demonstrated improved cardiac iron loading (20 ms), with no evidence of progression of ironloading in the brain.…”
mentioning
confidence: 99%
“…It has been used to treat cerebral iron loading in Freidrich Ataxia with clinical benefit and an acceptable side‐effect profile (Pandolfo & Hausmann, ). In patients with beta thalassaemia, combination therapy with DFP and deferoxamine has been shown to deplete hepatic and cardiac iron stores more effectively than DFP alone (Tanner et al , ). In our case, combination therapy was used for a limited time to good effect, to improve cardiac iron loading.…”
mentioning
confidence: 99%
“…The ability of deferiprone in effectively and rapidly removing excess cardiac iron load and in preventing iron accumulation appears to have caused a reduction in the cardiomyopathy‐ related mortality in thalassaemia (10, 17, 21, 22). Similarly, the introduction of deferiprone/deferoxamine combinations into many European and other countries has resulted in improvements in iron removal efficacy including an increase in the rate of depletion of excess cardiac iron load (23–26). Several deferiprone/deferoxamine combinations including the protocols suggested by the International Committee on Chelation (ICOC) consisting of oral deferiprone at 80–100 mg/kg/d and sc deferoxamine at 40–60 mg/kg for at least 3 d per week have been tested, leading to variable levels of iron removal which generally reflected the overall chelating drug dose (25–28).…”
mentioning
confidence: 99%
“…Similarly, the introduction of deferiprone/deferoxamine combinations into many European and other countries has resulted in improvements in iron removal efficacy including an increase in the rate of depletion of excess cardiac iron load (23–26). Several deferiprone/deferoxamine combinations including the protocols suggested by the International Committee on Chelation (ICOC) consisting of oral deferiprone at 80–100 mg/kg/d and sc deferoxamine at 40–60 mg/kg for at least 3 d per week have been tested, leading to variable levels of iron removal which generally reflected the overall chelating drug dose (25–28). Different synergistic and other mechanisms of iron binding and removal were applied to deferiprone and deferoxamine during the administration of the combination, which depend on the dose and timing of administration of each of the two drugs (8, 29, 30).…”
mentioning
confidence: 99%
“…Cardiac complications A significant improvement of the LVEF and the shortening fraction (SF) in comparison with the low values at baseline were reported in two papers (Origa et al , 2005; Kattamis et al , 2006). Recently, an abstract and later, a paper on a randomised placebo‐controlled, double blind trial, suggested that combined treatment is superior to DFO and placebo in removing myocardial iron in thalassaemia‐major patients (Tanner et al , 2005, 2007). However, there are no large retrospective or prospective clinical studies suggesting an effect on the reversal of heart failure in patients with initial or overt cardiomyopathy, except a single abstract presented at the 2006 ASH meeting (Lai et al , 2006).…”
mentioning
confidence: 99%